Pengaruh Pemanfaatan Teknologi Informasi, Kompetensi Sumber daya Manusia dan Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan Siswa - Wahyu Sugeng Suratman (Jurnal Bisnis Islam dan Kewirausahaan, 2022)
This study aims to determine the effect of the use of information technology, human resource competence, and internal control systems on the quality of financial reports at SMAN 1 Bantur. The number of samples used in this study as many as 20 respondents with the method of determining the sample is the purposive sampling method. Data was collected by distributing questionnaires to teachers and employees who had been in the financial/accounting management department, and processed using SPSS Statistics 25.0. The results of this study indicate that the use of information technology for human resource competence and internal control systems has a positive and significant effect on the quality of financial reports